Aerodynamic characteristics of high speed train under turbulent cross winds: A numerical investigation using unsteady-RANS method - Biadgo Asress Mulugeta; Simonović Aleksandar; Svorcan Jelena; Stupar Slobodan (FME Transactions, 2014)
Increasing velocity combined with reduced mass of modern high speed trains poses the question of influence of strong cross winds on its aerodynamics. Strong cross winds may affect the running stability of high speed trains via the amplified aerodynamic forces and moments. In this study, simulations of turbulent cross wind flows over the leading and end car of ICE-2 high speed train have been performed at different yaw angles The train aerodynamic problems are closely associated with the flows occurring around train. The flow around the train has been considered as incompressible and was obtained by solving the incompressible form of the unsteady Reynolds-Averaged Navier-Stokes (RANS) equations combined with the realizable k-epsilon turbulence model. Important aerodynamic coefficients such as the side force and rolling moment coefficients have been calculated for yaw angles ranging from -30° to 60° and compared to results obtained from wind tunnel tests. The dependence of the flow structure on yaw angle has also been presented.